Absolute added correlative coding: a novel higher-order modulation format for high-speed optical communication systems - Nguyen, Dong Nhat (2018)
A multilevel modulation format, namely absolute added correlative coding (AACC) is proposed to overcome the effect of fibre dispersion. A novel modulation and demodulation systems are proposed along with bit-error rate (BER) estimation technique. Transmission properties and system applications are also discussed. The research topics are categorised according to the type of the proposed multilevel signalling. It is worth mentioning that AACC can also be implemented with both NRZ and RZ pulse coding based upon the applications in order to optimise their performance.